The effect of the addition of cellulose on the quality and thermal properties of straw bedding = Wpływ dodatku celulozy na jakość i własności termiczne podłoża słomiastego - Słobodzian-Ksenicz, Oryna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The objective of the study was to determine the effect of the addition of recycled cellulose on the quality and temperature of the straw bedding. Starting from week 2 of the production cycle temperatures were registered and the degree of encrustation of both the cellulose and straw bedding was determined.
Keywords: podłoże słomiaste; dodatki celulozy; celuloza z recyklingu; własności termiczne; straw bedding; recycled cellulose; thermal properties